Effects of Wai Kru Muay Thai Training on Well-Being and Physical Fitness of People of all Ages - Amorntheap Wandee; Ban Chabairam; Suchart Homjan (Physical Education Theory and Methodology, 2023)
Study purpose. The study aimed to investigate the social, physical, and mental well-being of people of all ages in Buriram province and developed physical activities that apply to local people of all ages.